1995
DOI: 10.1136/gut.37.4.585
|View full text |Cite
|
Sign up to set email alerts
|

'Sticky' neutrophils, pathergic arthritis, and response to heparin in pyoderma gangrenosum complicating ulcerative colitis.

Abstract: Pyoderma gangrenosum is strongly associated with inflammatory bowel disease and exhibits pathergy, occurring at sites ofprevious minor trauma. A patient is presented with a 21 year history of extensive ulcerative colitis, who developed pyoderma gangrenosum and arthralgia while receiving high dose corticosteroids for active ulcerative colitis. The arthralgia exhibited pathergy affecting particularly the left temporomandibular joint, which was stressed by an asymmetric bite, and the left elbow, which had been fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…Gaffney and colleagues reported 10 patients, nine of whom responded, 4 and a large controlled Russian study reported a reduction in colectomy rate for severe colitis from 19.4% (control) to 6.2% (heparinized). 3 Recently we reported a patient with ulcerative colitis complicated by pyoderma gangrenosum who had a dramatic response to heparin 7 and speculated that the heparin might be exerting its effect via inhibition of neutrophil recruitment. We now report our further experience with the use of intravenous heparin in hospitalized patients with corticosteroidresistant ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Gaffney and colleagues reported 10 patients, nine of whom responded, 4 and a large controlled Russian study reported a reduction in colectomy rate for severe colitis from 19.4% (control) to 6.2% (heparinized). 3 Recently we reported a patient with ulcerative colitis complicated by pyoderma gangrenosum who had a dramatic response to heparin 7 and speculated that the heparin might be exerting its effect via inhibition of neutrophil recruitment. We now report our further experience with the use of intravenous heparin in hospitalized patients with corticosteroidresistant ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Interestingly, unfractionated heparin (UFH) has been found to reduce symptoms and improve healing in patients with GCS-refractive ulcerative colitis, 4±7 and also to be bene®cial against extraintestinal manifestations in ulcerative colitis. 8,9 In an uncontrolled study, 90% of the patients achieved complete remission. 4 However, this positive effect appeared to be dependent on concomitant SASP treatment, although these patients had not previously responded to SASP per se.…”
Section: Introductionmentioning
confidence: 99%
“…[123] Such effects were seen in patients with RA, [124] asthma [125] and ulcerative colitis. [126] A potential mechanism of action is inhibition of leukocyte extravasation through binding to the beta-2 integrin CD11b/CD18. [127;128] An intriguing possibility is the development of new agents that retain the antiinflammatory properties of heparin, but without the anticoagulant Kovesdy and Kalantar-Zadeh Page 10…”
Section: Sevelamer Hydrochloride-sevelamermentioning
confidence: 99%